Protective Effect of Immunization with Heat-Labile Enterotoxin in Gnotobiotic Rats Monocontaminated with Enterotoxigenic Escherichia coli - Klipstein, Frederick A. (1980)
The protective effect of active immunization with a purified preparation of the polymyxin-release form of Escherichia coli heat-labile enterotoxin (LT), administered using a parenteral prime and peroral boosts given after ablation of gastric secretion by means of cimetidine, was assessed in gnotobiotic rats which were challenged by monocontamination with enterotoxigenic strains of E. coli. Water transport was evaluated by the in vivo marker perfusion technique at weekly intervals over a 3-week period after contamination. Water transport in unimmunized control rats was consistently in absorption in those contaminated by a nontoxigenic strain, in secretion during only week 2 in those contaminated by an LT(+)/− strain, in secretion during weeks 2 and 3 in those contaminated by an LT(+)/ST(+) (heat-stable enterotoxin) strain, and consistently in absorption in those contaminated by an −/ST(+) strain. Rats immunized with a booster dosage of 250 μg had a significant increase (P < 0.001) in net water absorption as compared to unimmunized rats, with values in the borderline range of absorption, when challenged with either the LT(+)/− or LT(+)/ST(+) strains. Rats immunized with a 10-fold-higher boosting dosage had a significant increase (P < 0.001) in net water absorption as compared to those boosted at the lower dosage; water absorption was within the normal range. There was no difference between the ileal bacterial counts of unimmunized and immunized rats challenged by the various strains. These observations indicate that this immunization program provides complete protection in an animal model against challenge by intestinal contamination with enterotoxigenic strains of E. coli which produce LT, either alone or in combination with ST.